ESTIMATING THE AMOUNT OF THE WASTED WATER DUE TO FAULTY ACTIVITIES IN SOME AREAS IN DHI QAR/ SOUTHERN IRAQ - Hussein Khalefa Chlaib; Jalal Hameed Ali; Najm Abed Yasir; Alaa Ibrahim Badi; Jaber Hameed Muttair (University of Thi-Qar Journal of agricultural research, 2021)
Because of the poor water situation in Iraq in general and the southern governorates in particular requires prior consideration to find appropriate solutions. In this study، the researchers sought to estimate the amount of waste water in irrational and irrational ways in five vital areas within Thi-Qargovernorate, which are Qalat Suker, Al-Rifai, Al-Shatrah, Sug Al-Shuyukh and Al-Fuhud cities using the questionnaire distributed to citizens. The total amount of water wasted per month in these five areas due to the unemployed faucets is 1752660 liters. Because of the leakage of the water reservoirs without a roving، it is 901906480 liters، because washing the cars with the water hose is 952632 liters and keeping the faucets open during the cleaning of the teeth is 288845180 liters. Khartoum is 23163505 liters. The researchers concluded that very large quantities of drinking water are wasted daily due to erroneous activities by the population in the study areas where 1216620475 (one billion two hundred and sixteen million six hundred and twenty five hundred) liters per month are lost. Given that the average person in developing countries may need about 80 liters per day for all his needs، these amounts would have been wasted if it was used to provide 510000 citizens a day with drinking water